Hi... can anyone help me with this ?
looks simple, i know! but i forgot the method =(
basically i want to expand
the sum of r between r = 1 upto n-1
to get
1/2n(n-1)
how would i do this?
thanks!
Hi matlabnoob,
notice that $\displaystyle 1+2+3=(2-1)+2+(2+1)=2+2+2=3(2)$
and $\displaystyle 1+2+3+4+5=(3-2)+(3-1)+3+(3+1)+(3+2)=3+3+3+3+3=5(3)$
Therefore, this is the same as $\displaystyle (number\ of\ terms)(average\ value)$
For a large number of terms, simply take the average to be $\displaystyle \frac{1st\ term+last\ term}{2}$
Therefore $\displaystyle \sum_{r=1}^{n-1}r=\frac{1+n-1}{2}(n-1)=\frac{n(n-1)}{2}$
No, you cannot use the same method.
The previous one shows how to develop a formula for summing consecutive natural numbers.
If you want to sum consecutive squares, that's more involved.
You would need to understand the previous one quite well before attempting
to find a quick way to sum squares.
Here is a way to do it using "telescoping".
If you want to sum squares from r=1 to n-1, then you could use the following
$\displaystyle (2r+1)^3-(2r-1)^3=(2r+1)(2r+1)(2r+1)-(2r-1)(2r-1)(2r-1)$
$\displaystyle =(4r^2+4r+1)(2r+1)-(4r^2-4r+1)(2r-1)=$$\displaystyle (8r^3+4r^2+8r^2+4r+2r+1)-(8r^3-4r^2-8r^2+4r+2r-1)$
$\displaystyle =(8r^3+12r^2+6r+1)-(8r^3-12r^2+6r-1)=24r^2+2$
$\displaystyle \Rightarrow\ (2r+1)^3-(2r-1)^3=24r^2+2$
Telescoping
$\displaystyle r=1.......\ (2r+1)^3-(2r-1)^3=3^3-1^3$
$\displaystyle r=2.......\ (2r+1)^3-(2r-1)^3=5^3-3^3$
$\displaystyle r=3.......\ (2r+1)^3-(2r-1)^3=7^3-5^3$
$\displaystyle r=4.......\ (2r+1)^3-(2r-1)^3=9^3-7^3$
all the way to
$\displaystyle r=n-3....\ (2r+1)^3-(2r-1)^3=(2n-5)^3-(2n-7)^3$
$\displaystyle r=n-2....\ (2r+1)^3-(2r-1)^3=(2n-3)^3-(2n-5)^3$
$\displaystyle r=n-1....\ (2r+1)^3-(2r-1)^3=(2n-1)^3-(2n-3)^3$
When these are summed, all terms except $\displaystyle (2n-1)^3$ and 1 cancel.
Hence $\displaystyle \sum_{r=1}^{n-1}\left(24r^2+2\right)=(2n-1)^3-1$
2 summed n-1 times is 2(n-1)
Hence
$\displaystyle 24\sum_{r=1}^{n-1}r^2=(2n-1)^3-2(n-1)-1$
$\displaystyle \sum_{r=1}^{n-1}r^2=\frac{(2n-1)^3-2(n-1)-1}{24}$
If we sum all the way to n, this is more commonly known as the sum of squares
$\displaystyle \sum_{r=1}^nr^2=\frac{n(n+1)(2n+1)}{6}$